2007
DOI: 10.1089/met.2007.0021
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Risks among College Students: Prevalence and Gender Differences

Abstract: The college age and setting are a unique opportunity to monitor and intervene on early risk factors of chronic disease. Undiagnosed metabolic dysfunction is high and problematic in this age group. Unique gender differences in glucose metabolism warrant further research and should be considered in the design of intervention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
60
9
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 18 publications
12
60
9
4
Order By: Relevance
“…The findings of the current study corroborate what has been reported previously regarding the prevalence of overweight and obesity among the Hispanic adult population [11] and also among non-Hispanic college students [12][13][14][15]. Mean WC for predominantly White young adult males and females were 81.9 and 81.3 respectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings of the current study corroborate what has been reported previously regarding the prevalence of overweight and obesity among the Hispanic adult population [11] and also among non-Hispanic college students [12][13][14][15]. Mean WC for predominantly White young adult males and females were 81.9 and 81.3 respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, most of the research studies involving college students were limited by Caucasian or White population samples [12][13][14][15][16]. Evidence shows that various chronic diseases or related risk factors differ between races and ethnicities [17].…”
mentioning
confidence: 99%
“…Looking at specific components of MS, this study elicited the most prevalent component amongst the female students was central obesity (37.9%) which differs from most of the earlier studies (22)(23)(24)(25)(26)(27)(28)(29)(30) whereas, low HDL observed to be the second most predominant MS component (37.4%) amongst them. This finding differs from most of the earlier studies (22)(23)(24)(25)(26)(27)(28)(29)(30) which reported low HDL as the most prevalent MS component among female students.…”
Section: Discussioncontrasting
confidence: 81%
“…(24) (22) were higher than the results of the present study which may be due to the fact that most of these studies used NCEP-ATP III criteria for diagnosis of MS in which central obesity is not mandatory component (3).A remarkable observation in this study is the lower percentage (9.1%) of students having only the obligatory component of MS i.e. central obesity in comparison to students having any one of the other components in addition to central obesity (12.1%) which differs from earlier studies (22)(23)(24)(25)(26)(27)(28)(29)(30) implicating the increasing trend of other components of MS along with central obesity among the college students of Kolkata. Therefore, it may be stated that the students having high central obesity and/or any other MS components are at risk for the development of MS and subsequently they may become the victim of T2DM or CVD.…”
Section: Discussioncontrasting
confidence: 68%
“…15 This again indicates the importance of more intensive tests for early detection of risk of developing diabetes in future.…”
Section: Plasma Glucose Levelsmentioning
confidence: 99%